The Effect of Ten-week Ballroom Dance Therapy on Cognitive Abilities, Balance, and Perceived Stress Among Individuals over-60s - Lilla Barna; József Márton Pucsok; László Rátgéber; Kata Németh; Eszter Bíró; László Balogh, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Nowadays, aging is a popular research topic. Several articles describe the positive effects of dance and music therapies on older individuals' cognitive and physical abilities. Our research examined the effects of ten-week dance therapy on senior participants over 60s. We also assessed their cognitive abilities, physical endurance, and perceived stress levels. The Vienna Test System, Determination Test (VTS DT) was performed to assess the cognitive stress for 12 minutes. We measured a significant increase in the effect of the training program. We observed an elevation in mean pre-training values. After the intensive ballroom dance program, there was also a significant improvement, in mean score. We also examined the acute effect of a single dance class. We observed a significant improvement in acute values. Participants completed the Perceived Stress Questionnaire (PSS-14) and a Flamingo balance test before and after the dance program. We used a paired T-test to determine the effect of dance therapy on participants' perceived stress. The results indicated a significantly improved ability to balance after completing the dance program. We may conclude that the dance program has improved the current cognitive abilities of the elderly. Practical implications of our study includes improvement the quality of life, and support healthy lifespan of the elderly. Future studies, with higher number of participants, involving various physical activities,would be helpful to support our hypothesis.